Efficiency of Germination and Vigour Tests in Predicting Field Performance of Different Genotypes of Maize (Zea Mays L.) - Olosunde, Akinloye Adam (2015)
Eighteen varieties of maize (Zea mays L.) were used to evaluate the efficacy of germination and vigour tests in predicting maize emergence under field conditions as well as to investigate whether differential response to the tests exist among the maize varieties. The study was designed to establish which among the tests could be used to reliably predict field emergence of maize.